Etične dileme novodobnega marketinškega hibrida - Lukač, Petra (Akademija MM, 2014)
This paper draws on a recent conceptual proposal to theoretically positioned business practices that merge principles of social marketing with commercial business models. This modern marketing hybrid is called commercial social marketing. It utilizes marketing techniques to encourage a behavioural or attitudinal change in the target group, aiming to achieve a social goal that is conducive to a more fundamental corporate goal (Anker and Kappel, 2011). This paper has two goals; first, it aims to position commercial social marketing in comparison to other similar concepts like social marketing, corporate societal marketing, and put related marketing within the context of Slovene marketing terminology. Second, it sets a research framework for identifying the presence of commercial social marketing campaigns in Slovene marketing practice, and for describing their key features. The research shows that not many campaigns in Slovenia correspond to the criteria of commercial social marketing. Rather, more campaigns could be described as commercial social advertising, cause related marketing or other forms of corporate social marketing. Since 2004 up to 2013, only three campaigns in Slovenia were consistent with all six commercial social marketing criteria, namely "5 na dan", "Zdravo je pravo" and "Ego Slim & Vital". These three campaigns encourage behavioural or attitudinal change in their target groups, but they also evidently show that their fundamental concern lies with business motives (i.e. profit increase, differentiation on the market, competitive advantage, improvement of corporate image and brand etc.), rather than social motives (achieving social change in relation to particular social problem). Thus they provoke a number of ethical concerns, similarly as commercial social marketing campaigns elsewhere in the world.
Keywords: družbeni problemi; družbeni vidik; marketing; trženje; tržno komuniciranje